Comparison of Serum Albu-min Levels in The Breast Milk of Breastfeeding Infants Aged 1-3 Months and 4-6 Months - Mudjihartini, Ninik (Indonesian Journal of Medical Chemistry and Bioinformatics, 2023)
Abstract: Background: Serum albumin is the most abundant plasma protein in the blood, contributing to maintaining colloid osmotic pressure and binding substances that are poorly soluble in plasma so that they can be distributed throughout the body. Serum albumin levels in breast milk can vary, influenced by various factors such as the lactation phase (age of the baby), number of parities, age and body mass index (BMI) of the mother. This study aims to determine the comparison of serum albumin levels in breast milk of mothers who breastfeed infants aged 1-3 months and 4-6 months and to find the relationship with the number of parities, age and BMI of the mother. Method: Cross-sectional design experimental study, breast milk samples as stored biological fluids were obtained from 58 mothers at the Petamburan and Cilincing Health Centers. Serum albumin levels were measured with the Bromocresol Green (BCG) kit. Results: The results showed that breast milk in the earlier lactation period, namely at 1-3 months, had significantly higher serum albumin levels compared to the serum albumin levels in the 4-6 months age group (p=0.002). Serum albumin levels in breast milk for infants aged 1-3 months did not correlate with mother's parity (p=0.428) and mother's age (p=0.881), but had a significant positive correlation with mother's BMI (p=000). Serum albumin levels in breast milk in the 4-6 months age group did not correlate with mother's parity (p=0.823) and mother's age (p=0.581) but had a strong positive correlation with maternal BMI (p=0.000). Conclusion: Breast milk serum albumin levels are affected by the lactation phase (age of the baby), namely at the age of 1-3 months the baby increases significantly compared to the age of 4-6 months. The level of serum albumin in breast milk is related to the mother's BMI, which increases with increasing mother's BMI.